Muslim private higher educational institutions in Malaysia: issues and challenges - Hashim, Rosnani (International Institute of Advanced Studies (IAIS) Malaysia and Pluto Press (London), 2012)
Privatisation of higher education is a global trend. There is an increasing demand for higher education due to the nature of work and economy today, and public universities and colleges cannot meet the demand with their limited financial resources from the government. Private higher education institutions (PHEI) seem to be the most attractive alternative to public universities and colleges in opening greater access to higher education. Malaysia is no exception, having about 25 private universities, 22 private university colleges and 410 private colleges and institutes. About a forth of these PHEIs are Islamic institutions going by the name of the institutions or their ownership. However, private higher education institutions have their own issues and challenges. The most serious of them are preserving the philosophical goal of a balanced and integrated education despite market demands and sustaining its operation financially amidst a competitive environment. Yet, there are several opportunities for Islamic PHEIs especially in terms of international collaboration and exchanges. This article is an attempt to examine these issues and challenges or opportunities.